User Satisfaction and Net Benefits in Digital Insurance Placement Systems: An Extended DeLone and McLean IS Success Model in Indonesian Brokerage Firms - Shan Thi; Viany Utami Tjhin (Politeknik Siber Cerdika Internasional, 2026)
Background: Insurance brokerage operations in Indonesia continue to rely on manual, siloed processes that reduce operational efficiency and service quality. Despite increasing digital transformation adoption, empirical evidence on digital system success in insurance brokerage remains limited. Objective: This study investigates the factors influencing user satisfaction and net benefits from a digital insurance placement system in Indonesian brokerage firms, extending the DeLone and McLean IS Success Model with Digital Capability and Cybersecurity. Methods: A survey method was used with a total of 100 unique surveys completed by different authorized users from partner insurance companies, which included underwriters and marketing officers working directly with the digital insurance placement platform. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was applied to analyze the data. Results: The results of this study show that System Quality, Service Quality, and Digital Capability are the significant variables that affect User Satisfaction, while Information Quality and Cybersecurity have no significant effect. Additionally, since User Satisfaction has a significant positive effect on Net Benefits, it leads to improved operational efficiency, reduced placement cycles, and increased accuracy in decision-making. Conclusion: This research expands the literature by extending the IS success framework with digital capability and cybersecurity and offers practical insights for managerial practice to leverage digital system deployment, build technological readiness, and improve competitive advantage in a digitalized insurance ecosystem.